La planeación pedagógico-didáctica implementada en el área de inglés en las comunas 1 y 2 de Bucaramanga, que atiende estudiantes en condición de vulnerabilidad en los niveles de básica y media: retos y oportunidades (2021)
The Colombian educational policy implemented in the period 2002- 2018 established actions for the educational attention of populations framed in the principles of inclusion and equity, focusing its interest on populations in conditions of vulnerability, and developing tools to strengthen school practices and improve the learning of the population. The objective of the research in the preliminary phase is to characterize the didactic units implemented in the English area in communes 1 and 2 of Bucaramanga, which serve vulnerable students at the elementary and middle school level. To fulfill the purpose, an exploratory and descriptive research was proposed, focused on the analysis of the content of Colombian educational legislation for the definition of emerging categories of analysis; These categories were used to assess the pedagogical-didactic planning of the institutions. It was found that the planning in the area of English projected for the vulnerable population focuses on the definition of the evaluation, and relevant aspects of the frame of reference of the National Plan for Bilingualism are neglected, such as: the inclusion of basic learning rights, implementation of the teaching material and the functions of the second language. It is concluded that planning is essential to adequately articulate the intended curriculum —which is configured based on the regulations analyzed—, the applied curriculum —which is based on planning— and the achieved curriculum —which corresponds to that expressed by students in the massive assessment tests—, which is necessary for the effective acquisition of a second language. Finally, based on the results of the characterization, challenges and opportunities arise from pedagogical-didactic planning for the area, in order to direct actions to fulfill the objectives of the National Plan for Bilingualism.